2009
DOI: 10.1002/cncr.23985
|View full text |Cite
|
Sign up to set email alerts
|

Extent of lymphadenectomy and outcome for patients with stage I nonsmall cell lung cancer

Abstract: BACKGROUND: It is uncertain whether lymphadenectomy (LA) affects overall survival (OS) or disease‐free survival (DFS) rates for patients with stage I nonsmall cell lung cancer (NSCLC), as is the optimal number of lymph nodes that should be recovered. METHODS: There were 24,273 patients with stage I NSCLC diagnosed from 1992 to 2002 who were included in the Surveillance, Epidemiology, and End Results database and who underwent a definitive surgical procedure. Median follow‐up was 35 months. RESULTS: For the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
94
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 25 publications
12
94
2
1
Order By: Relevance
“…Overall , 40 % had one positive LN, 35% had two to three positive LNs, 21% had four to eight positive LNs, and 4% had more than eight positive LNs. The median (interquartile range) of the number of LNs sampled was 14 (12)(13)(14)(15)(16)(17)(18)(19). The baseline characteristics of patients in the four LN groups are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall , 40 % had one positive LN, 35% had two to three positive LNs, 21% had four to eight positive LNs, and 4% had more than eight positive LNs. The median (interquartile range) of the number of LNs sampled was 14 (12)(13)(14)(15)(16)(17)(18)(19). The baseline characteristics of patients in the four LN groups are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…14,[25][26][27][28] Although the LN ratio may be applied among patients with a low number of LNs sampled, current data suggest that staging based on , 10 LNs is not accurate. [15][16][17][18][19] Additionally, the number of positive LNs is a more direct and intuitive measure of the extent of LN involvement, and thus may be more readily adapted into clinical practice. Although the number of positive nodes and the LN ratio have shown to be valid prognostic factors of N1 NSCLC, both measures are sensitive to the total number of LNs evaluated during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung cancer, Ludwig and associates [21] recommended that an evaluation of nodal status should include somewhere between 11 to 16 lymph nodes. The study from Varlotto et al [22] evaluated 24,273 patients with stage I NSCLC who underwent a definitive surgical procedure. The optimal number of sampled lymph nodes ensuring the highest staging accuracy should be not less than 11 N1 dissection and 7 N2 dissection lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Two large retrospective reviews conducted by Gajra et al [23] and Doddoli et al [24] analyzing 442 and 465 patients, respectively, found that removal of at least 6 lymph nodes (for patients with six or fewer lymph nodes assessed, DFS was 52%, and the patients with more than six lymph nodes assessed had DFS of 75% at 5 years (p= 0.001)) and dissection of at least 3 mediastinal stations or removal of 10 lymph nodes and dissection of at least 2 mediastinal stations, were associated with improved survival [22] (Table 1).…”
Section: Introductionmentioning
confidence: 99%